Salicylic acid-induced glutathione status in tomato crop and resistance to root-knot nematode, Meloidogyne incognita (Kofoid & White) Chitwood - Hari C. Meher; Vijay T. Gajbhiye; Ghanendra Singh (Journal of Xenobiotics, 2011)
Salicylic acid-(SA) is a plant defense stimulator. Exogenous application of SA might influence the status of glutathione-(GSH). GSH activates and SA alters the expression of defense genes to modulate plant resistance against pathogens. The fate of GSH in a crop following SA treatment is largely unknown. The SA-induced profiles of free reduced-, free oxidized-(GSSG) and protein bound-(PSSG) glutathione in tomato crop following foliar treatment of transplant at 5.0-10.0 μg mL–1 were measured by liquid chromatography. Resistance to root-knot nematode, Meloidogyne incognita damaging tomato and crop performance were also evaluated. SA treatment at 5.0-10.0 μg mL–1 to tomato transplants increased GSH, GSSG and PSSG in plant leaf and root, more so in leaf, during crop growth and development. As the fruits ripened, GSH and PSSG increased and GSSG declined. SA reduced the root infection by M. incognita, nematode reproduction and thus, improved the resistance of tomato var. Pusa Ruby, but reduced crop growth and redox status. SA at 5.0 μg mL–1 improved yield and fruit quality. The study firstly linked SA with activation of glutathione metabolism and provided an additional dimension to the mechanism of induced resistance against obligate nematode pathogen. SA increased glutathione status in tomato crop, imparted resistance against M. incognita, augmented crop yield and functional food quality. SA can be applied at 5.0 μg mL–1 for metabolic engineering of tomato at transplanting to combine host-plant resistance and health benefits in formulating a strategic nematode management decision.